UMP VC appointed Guest Professor to China’s University Hebei - UMP, PNC
The Vice-Chancellor (VC) of Universiti Malaysia Pahang (UMP), Professor Dato’ Dr. Daing Nasir Ibrahim, was honored by China’s University Hebei when he was recently appointed as its Guest Professor.